2020
DOI: 10.1109/led.2019.2953245
|View full text |Cite
|
Sign up to set email alerts
|

H-Terminated Polycrystalline Diamond p-Channel Transistors on GaN-on-Silicon

Abstract: In many semiconductor technologies, including GaN, the lack of p-channel devices is a major obstacle for complementary operations. Here, we demonstrate highperformance polycrystalline diamond p-channel transistors on GaN-on-Si. Following the optimization of the microwave-plasma chemical-vapor-deposition of diamond on GaN, the polycrystalline layer was hydrogenated to form a 2D hole-gas at the surface, acting as p-channel. Relying on a rather simple fabrication process, these devices exhibited excellent electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The maximum sheet carrier concentration we have achieved on a similar PC diamond in our experiments is 6.78 × 10 13 cm −2 with a mobility of 1.42 cm 2 /V•s. The measured characteristics for 2DHG are comparable to the numbers reported for the PC diamond on AlGaN/GaN substrate so far, 27 except that our diamond layer was much thinner (∼1 μm) with a smaller grain size (∼600 nm). A thinner diamond is preferred for integration on top of heterostructures like AlGaN/GaN HEMTs to avoid building enormous residual stress on the interface.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The maximum sheet carrier concentration we have achieved on a similar PC diamond in our experiments is 6.78 × 10 13 cm −2 with a mobility of 1.42 cm 2 /V•s. The measured characteristics for 2DHG are comparable to the numbers reported for the PC diamond on AlGaN/GaN substrate so far, 27 except that our diamond layer was much thinner (∼1 μm) with a smaller grain size (∼600 nm). A thinner diamond is preferred for integration on top of heterostructures like AlGaN/GaN HEMTs to avoid building enormous residual stress on the interface.…”
Section: Methodssupporting
confidence: 84%
“…In a separate study, the role of PC diamond as a heat spreader was also discussed, making this combination even more desirable for various applications . Unlike the SC diamond, the PC diamond can be directly grown on III-nitride semiconductors, enabling a pathway for monolithic integration of diamond hole FET and GaN HEMT on a single substrate, which forms the foundation of this study. The PC diamond was grown on GaN HEMT using the microwave plasma chemical vapor deposition (MPCVD) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Our measured TBR which was significantly low due to the atomically smooth interface allows phonon transport from the hot spot in the GaN channel to the diamond layer with minimum possible scattering and discontinuity in the temperature profile. The TC of the 2 μm-thick diamond with about the same grain size was measured to be 638 ± 48 W/m K, which is among the highest reported TC for diamond on GaN 12,13 in literature studies and close to the theoretical TC for diamonds with a ∼2 μm grain size. 23 Decreasing the diamond/Si 3 N 4 /GaN TBR from 6.5 m 2 K/GW 27−29 to 3.1 m 2 K/GW and increasing the diamond thickness from 1 to 2 μm for higher TC at the same time reduce the overall channel thermal resistance to ∼6.2 m 2 K/GW.…”
Section: Resultsmentioning
confidence: 98%
“…9−11 Excellent research studies have been reported on integrating diamond and GaN for thermal management. 12,13 In one of the approaches, the substrate is bonded with SC diamond, while in another, chemical vapor-deposited (CVD) PC diamond is grown on the backside of the substrate. 14,15 In contrast to the backside diamond integration, we have presented our approach of integrating PC diamond on top of the device channel by direct CVD growth.…”
Section: Introductionmentioning
confidence: 99%
“…2 A lower cost approach has been proposed by integrating diamond on the cost-effective GaN-on-Si substrates, on which diamond transistors were demonstrated on AlGaN/GaN-on-Si substrates with excellent device characteristics, even without polishing of the rough diamond surfaces. 18 However, the high roughness of as-grown diamond imposes limitations for the wafer processing using planar fabrication methods. Therefore, polishing is an essential step to obtain smooth diamond surfaces and reliable fabrication processes.…”
Section: ■ Introductionmentioning
confidence: 99%